2019
DOI: 10.1088/1755-1315/385/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Online Mapping and GIS Mobile Healthcare Systems for Intensifying Low-and-Middle-Income Community Accessibility

Abstract: Systematic healthcare facilities and accessibility system in developing countries are mostly located in urban areas instead of rural areas, causing inconvenience to low-and-middle-income residents to reach healthcare centres. Therefore, an innovative mapping and geomobile application or app is developed for the modernization of healthcare systems in Pulau Indah, Klang Malaysia. This study aimed to provide relevant geoinformation of the healthcare centres and the optimum route to the nearby healthcare facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Pregnancy monitoring system: Three studies reported the mobile app monitoring tools deployed in India and Pakistan to monitor pregnancy [77][78][79]. The Daksh system monitored intra partum care [79]; the Continuum of Care mhealth platform was used for pregnancy registration and monitoring care [80], and a mhealth app in Pakistan managed the clinical workforce and provision of health care equipment [81]. Healthcare facilities app: A mobile app in Malaysia provided information about local facilities with maps, health care information, cost estimation, and online survey feedback [81].…”
Section: Exemplar Digital Health Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy monitoring system: Three studies reported the mobile app monitoring tools deployed in India and Pakistan to monitor pregnancy [77][78][79]. The Daksh system monitored intra partum care [79]; the Continuum of Care mhealth platform was used for pregnancy registration and monitoring care [80], and a mhealth app in Pakistan managed the clinical workforce and provision of health care equipment [81]. Healthcare facilities app: A mobile app in Malaysia provided information about local facilities with maps, health care information, cost estimation, and online survey feedback [81].…”
Section: Exemplar Digital Health Interventionsmentioning
confidence: 99%
“…The Daksh system monitored intra partum care [79]; the Continuum of Care mhealth platform was used for pregnancy registration and monitoring care [80], and a mhealth app in Pakistan managed the clinical workforce and provision of health care equipment [81]. Healthcare facilities app: A mobile app in Malaysia provided information about local facilities with maps, health care information, cost estimation, and online survey feedback [81]. ICT in community pharmacies: ICT features such as electronic health records, electronic payment systems, accounting and logistics software, barcode reading system for medicines, online stores, as well as systems for communication with patients (Whatsapp, SMS) were implemented in pharmacies in Malaysia.…”
Section: Exemplar Digital Health Interventionsmentioning
confidence: 99%
“…In developing nations, systematic healthcare facilities and accessible systems are largely centered in metropolitan regions rather than in rural areas, causing inconvenient access to healthcare centres for low-and middle-income citizens [4]. Generally, driving and walking (especially in rural areas) are the two main commutation procedures used to arrive at a health centre.…”
Section: Introductionmentioning
confidence: 99%
“…This research has shown promising results in helping patients treat a variety of diseases [17]. The article by Zain Rashid et al [18] presents quite different research in the field of healthcare. The given project aimed to provide geo-information on healthcare and also to show the optimal route to nearby healthcare facilities in Pulau Indah, Klang Malaysia [18].…”
mentioning
confidence: 99%